The influence of school principals' leadership on teacher performance - Toni, Toni; Maria, Haratua Tiur; Karolina, Venny (Universitas Negeri Semarang, 2023)
In the field of educational management, the performance of teachers is a critical determinant of the overall quality of education. Recognizing this, recent research has increasingly focused on identifying factors that influence teacher performance. Among these, principal supervision and teaching planning are considered vital elements. This study aims to determine the influence of the importance of principal supervision and teaching planning on teacher performance, both partially and simultaneously. The research approach uses a quantitative approach, namely associative (correlational) research with a sample of 20 respondents from 20 teachers at Junior High School in 5 Ledo as a population. Data processing using multiple linear regression analysis. The results showed that there was a positive influence of principal supervision and teaching planning both partially and simultaneously as evidenced by the results of t count of 1.870 there was an influence of other variables of 0.071. In conclusion, the higher and better the principal's supervision and teaching planning provided, the higher the performance of teachers shown at Junior High School in 5 Ledo. The novelty of this research lies in its specific focus on the simultaneous impact of principal supervision and teaching planning on teacher performance within an Indonesian Junior High Schoolcontext. While previous studies have examined these factors individually, this research innovatively assesses their combined effect, providing a more holistic understanding of the dynamics influencing teacher performance.